Fluoroscopy usage in contemporary interventional electrophysiology: Insights from a European registry. Issue 1 (21st November 2020) - Kosiuk, Jedrzej; Fiedler, Lucas; Ernst, Sabine; Duncker, David; Pavlović, Nikola; Guarguagli, Silvia; Stegmann, Clara; Miskowiec, Dawid; Garcia, Rodrigue; Russo, Vincenzo; Yakushev, Andriy; Szegedi, Nándor; et al.
Abstract: Background: Fluoroscopy has been an essential part of every electrophysiological procedure since its inception. However, till now no clear standards regarding acceptable x‐ray exposure nor recommendation how to achieve them have been proposed. Hypothesis: Current norms and quality markers required for optimal clinical routine can be identified. Methods: Centers participating in this Europe‐wide multicenter, prospective registry were requested to provide characteristics of the center, operators, technical equipment as well as procedural settings of consecutive cases. Results: Twenty‐five centers (72% university clinics, with a mean volume of 526 ± 348 procedures yearly) from 14 European countries provided data on 1788 cases [9% diagnostic procedures (DP), 38% atrial fibrillation (AF) ablations, 44% other supraventricular (SVT) ablations, and 9% ventricular ablations (VT)] conducted by 95 operators (89% male, 41 ± 7 years old). Mean dose area product (DAP) and time was 304 ± 608 cGy*cm 2, 3.6 ± 4.8 minutes, 1937 ± 608 cGy*cm 2, 15.3 ± 15.5 minutes, 805 ± 1442 cGy*cm 2, 10.6 ± 10.7 minutes, and 1277 ± 1931 cGy*cm 2, 10.4 ± 12.3 minutes for DP, AF, SVT, and VT ablations, respectively. Seven percent of all procedures were conducted without any use of fluoroscopy. Procedures in the lower quartile of DAP were performed more frequently by female operators (OR 1.707, 95%CI 1.257‐2.318, P = .001), in higher‐volume center (OR 1.001 per one additional procedure, 95%CI 1.000‐1.001, P = .002), with the use of 3D‐mapping system (OR 2.622, 95%CI 2.053‐3.347, P < .001) and monoplane x‐ray system (OR 2.945, 95%CI 2.149‐4.037, P < .001). Conclusion: Exposure to ionizing radiation varies widely in daily practice for all procedure. Significant opportunities for harmonization of exposure toward the lower range has been identified.